A Improving the Nutritional Status of Stunted Children through Providing Additional Fish-Based Food: Stunting - Muhammad Ridho Nugroho; Trisko Defriansya; Henita Andriani; Asron Erwandi; Feri Herita Erawani (Indonesian Journal of Health Research and Development, 2024)
For toddlers who are stunted, processed fish food can be utilized as an additional source of healthy nutrients. This study set out to assess how supplementing fish-based meals affected the nutritional status of toddlers who were stunted. 37 stunted toddlers in Lubuklinggau City received Additional Fish-Based Food for ninety days, from September to December 2023, as part of the study's sample. This research approach used an experimental design with a pre- and post-test strategy without control. Pairwise comparison tests were employed to do statistical analysis by evaluating the nutritional status of toddlers prior to and following the intervention. The research will be finished by December 2023. 6 (16.21%) of the toddlers had improved to a normal nutritional state, according to the data. The nutritional status of toddlers differed significantly before and after the intervention, as evidenced by a p-value of 0.000 (0.05). Thus, it can be said that giving toddlers extra fish-based meal treatments for ninety days can enhance their nutritional status and lower the incidence of stunting in the toddlers who are the target population.